Surgical models and perioperative care in swine - Swindle, M. Michael; McCrackin, Mary Ann (Henry Stewart Talks, 2015)
Different swine breeds used in research, Swine physiology from a surgical standpoint, Preoperative & Postoperative care, Anesthetic protocols for swine, Pain assessment & Analgesia, Aseptic techniques, Wound protection and Humane restraint, In depth look at porcine surgical models in various physiological systems
Reviewed at 2024/07/02